Newly Excavated Confucian Bamboo Manuscripts and Related Research - Sixin DING; Qiannan ZHAO (Asian Studies, 2024)
The primary purpose of this article is to comprehensively survey the research on excavated Confucian texts from the past 30 years. Newly excavated Confucian manuscripts are seen in such collections as those from Guodian 郭店, Shangbo 上博, Tsinghua 清華, Anda 安大, and Haihun 海昏. In terms of their content, they each have their own focus and characteristics. Among these bamboo manuscripts there is a large number dedicated to the Shijing 詩經, the Shujing 書經, the Liji 禮記, the Yijing 易經, and to Kongzi 孔子 making them of great importance. At present, research on the Guodian and the Shangbo manuscripts is mostly completed and that into the Tsinghua collection is making large strides while research into the Anda collection is just beginning to develop. Among all this research, one of the weakest areas revolves around the explanation and discussion of Confucian thought and related problems. This includes textual evidence in the form of excavated Confucian texts that provide a foundation for “leaving behind the age of doubting antiquity” (zouchu yigu shidai 走出疑古時代) and the related debates carried out by scholars are beneficial to transmitting and revising this theory.